A Comparative Analysis of Strategies for the Formation of Civic Identity in Russia and China - N. B. Pomozova (Vestnik MGIMO-Universiteta)
The article describes the methods of management of civic identity formation in Russia and China during the period of transformation processes, which have affected both countries in the end of XX – beginning of XXI centuries. The author identifies three distinct periods of civic identity formation of modern Russians and concludes, that the nature of civic identity strategy had rather chaotic and spontaneous nature. At the same time, China has also faced the need to reform economic and social systems, but has chosen the evolutionary path with a well-planned strategy of civic identity formation management.